Single administration vaccines: delivery challenges, in vivo performance, and translational considerations - Kyprianos Michaelides; Maruthi Prasanna; Raj Badhan; Afzal-; Adam Walters; M. Keith Howard; Pawan Dulal; Ali Al-Khattawi (Taylor & Francis Group, 2023)
Introduction With a limited global supply of vaccines and an increasing vaccine hesitancy, improving vaccination coverage has become a priority. Current vaccination regimes require multiple doses to be administered in a defined schedule where missed doses may lead to incomplete vaccine coverage and failure of immunization programmes. As such, there is an ever-increasing demand to convert multi-dose injectable vaccines into single-dose formats, often called single administration vaccines (SAVs). Areas covered This review summarizes recent developments in the field of SAVs, with a focus on pulsatile or controlled-release formulations. It will identify the technical challenges, translational as well as commercial barriers to SAVs development. Furthermore, the progress of SAV formulations for hepatitis B and polio vaccines will be reviewed thoroughly as case studies, with a focus on the development challenges and the preclinical immunogenicity/reactogenicity data. Expert opinion Despite the efforts to develop SAVs, few attempts have advanced to Phase-I trials. Considering the SAV development journey and bottlenecks, including commercial barriers from the early stages, may overcome some of the hurdles around the technology. The renewed global focus on vaccines since the COVID-19 pandemic could facilitate development of a new generation of technologies for pandemic preparedness including strategies for SAVs.